Identification and containment of a cluster of two Bacillus cereus infections in a neonatal intensive care unit - Papan, Cihan (The Canadian journal of infectious diseases & medical microbiology, 2019)
We report a cluster of invasive Bacillus cereus infections in a neonatal intensive care unit. We describe the clinical course of two infected patients, one of whom died of severe pneumonia after successfully being weaned from ECMO. Environmental analyses failed to yield a common source. Molecular characterization confirmed the homogeneity of both isolates. Rigorous hygiene control and adequate therapy enabled the containment of the cluster.